Transient effects of carotid baroreflex stimulation via the neck chamber device on central venous pressure. Issue 12 (16th November 2021) - Quarti‐Trevano, Fosca; Seravalle, Gino; Spaziani, Domenico; Vanoli, Jennifer; Mancia, Giuseppe; Grassi, Guido
Abstract: We examined in 11 young subjects (age 29.7±3.6 years, mean±SEM) whether carotid baroreceptor stimulation via the neck chamber device may affect central venous pressure (CVP), thus potentially involving other reflexogenic areas in the examined responses. Application of progressively greater neck chamber subatmospheric pressures caused a progressive lengthening in RR interval, which reached a peak at the maximal value of negative neck chamber pressure applied. This was accompanied by significant and progressively greater reduction in CVP values when the data were calculated considering the early changes occurring within the first 2 seconds of the stimulus. There was a weak correlation between the early changes in CVP and the RR interval responses when all stimuli were pooled together (r = 0.32, P  < .05). The results of the present study suggest that the neck chamber technique employed to assess carotid baroreceptor‐heart rate sensitivity can transiently affect via the CVP reduction cardiopulmonary receptors activity, which may participate at the integrated reflex responses.